Pelatihan Kewirusahaan: Punya Usaha Sendiri, Mengapa Tidak: Koperasi Serba Usaha “Aneka Usaha” Karangbendo, Kapanewon, Banguntapan Bantul - R. Nur Budi Setiawan; MG. Suwarni (Universitas Kristen Indonesia Toraja, 2024)
Objective to mobilize local communities to want to become entrepreneurs by developing all the potential around them, especially for members of the multi-business cooperative